High-density perimetry in the assessment of foveal avascular zone and macular structure in glaucoma - Gustavo Coelho Caiado; Gustavo Albrecht Samico; Gilvan Vilarinho da Silva Filho; Sergio Henrique Teixeira; Tiago Santos Prata; Carolina Pelegrini Barbosa Gracitelli; Augusto Paranhos (PLoS ONE, 2025)
Purpose To evaluate the association between foveal avascular zone (FAZ) parameters (area, perimeter and circularity) with macular high density perimetry (Octopus Macular program), macular vessel density (mVD) and ganglion cells layer thickness (GCLT) in glaucoma patients. Methods This cross-sectional study included 89 eyes from 57 glaucoma patients. All participants underwent high-density perimetry (Octopus 900 Macular and G programs). FAZ metrics and mVD were obtained via Optical Coherence Tomography Angiography (OCTA) (Triton, Topcon), and GCLT was measured across global, superior, and inferior sectors. FAZ parameters were automatically extracted using ImageJ with axial length correction. Structure–structure and structure–function associations were assessed using mixed-effects linear regression models, adjusting for inter-eye correlation, age, and GCLT when appropriate. Results Mean age was 66.67 ± 7.49 years old. FAZ area and perimeter were significantly associated with mean defect of macular program (mMD), central mVD, and GCLT (p < 0.05). FAZ area remained significantly associated with GCLT even after controlling for age (p < 0.05). FAZ perimeter and circularity were independently associated with age. FAZ perimeter and circularity were mainly age-related, while area was linked to glaucomatous damage. FAZ parameters were more strongly related to superior than inferior GCLT. Glaucoma severity was categorized using Brusini’s Glaucoma Staging System. Higher mMD values were observed in more advanced stages of glaucoma. Conclusions FAZ morphology reflects both glaucomatous damage and age-related vascular changes. By controlling for confounding variables, this study reinforces the role of FAZ metrics as complementary biomarkers for assessing structure-function relationships in glaucoma. High-density macular perimetry further improves spatial correspondence with anatomical alterations.